2005
DOI: 10.1128/aem.71.11.6816-6822.2005
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157:H7 in Environments of Culture-Positive Cattle

Abstract: Outbreaks of Escherichia coli O157:H7 disease associated with animal exhibits have been reported with increasing frequency. Transmission can occur through contact with contaminated haircoats, bedding, farm structures, or water. We investigated the distribution and survival of E. coli O157:H7 in the immediate environments of individually housed, experimentally inoculated cattle by systematically culturing feed, bedding, water, haircoat, and feed bunk walls for E. coli O157:H7 for 3 months. Cedar chip bedding wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
2
31
1
Order By: Relevance
“…These findings support the idea that if reoccurring colonization was the cause for intermittent shedding, those patterns most likely resulted from the steers' social interactions and their contact with the ropes, which were considered to be representative of their environment. Several studies have reported that this intermittent environmental exposure can be caused by contaminated water, feed sources, or bedding (15,19,30,48). However, in this study contaminated water was not detected, minimal detection was found in the feed troughs, and no bedding was provided to the steers.…”
Section: Discussioncontrasting
confidence: 43%
“…These findings support the idea that if reoccurring colonization was the cause for intermittent shedding, those patterns most likely resulted from the steers' social interactions and their contact with the ropes, which were considered to be representative of their environment. Several studies have reported that this intermittent environmental exposure can be caused by contaminated water, feed sources, or bedding (15,19,30,48). However, in this study contaminated water was not detected, minimal detection was found in the feed troughs, and no bedding was provided to the steers.…”
Section: Discussioncontrasting
confidence: 43%
“…If plasmids impose a net fitness cost, then plasmid-free segregants will eventually "sweep" through the population and replace the resistant plasmid-bearing strains. Elimination of resistance genes themselves from a plasmid can lower the fitness burden of a plasmid (3,11), which can also lead to a selective sweep of a less versatile plasmid.…”
mentioning
confidence: 99%
“…The total effect of increasing the frequency of bedding replacement/cleaning and water trough cleaning is considered a hygienic measure in reducing the prevalence of VTEC O157 infected animals. The data of Scott et al [22] and Davis et al [11] were used to determine the bacterial death rate in water and bedding materials respectively, using formula 1:…”
Section: Hygienementioning
confidence: 99%
“…Using formula 1, we estimated that increasing the frequency of replacing bedding (in a straw yard housing system) or cleaning (in a cubicle housing system) from one to two times per week results in a death rate of 0.46 infectious units per day. This was done by fitting an exponential distribution to the data (i.e., initial number of CFU in the environment corresponding to the time unit (day) of the study) reported by Davis et al [11]. Following the same procedure and using the data obtained by Scott et al [22], it was estimated that increasing the frequency of cleaning the water troughs from once per month to four times per month results in a death rate of 0.17 infectious units per day.…”
Section: Hygienementioning
confidence: 99%